2006
DOI: 10.1128/jb.00771-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Essential Gene ofListeria monocytogenesInvolved in Teichoic Acid Biogenesis

Abstract: Listeria monocytogenes is a facultative intracellular gram-positive bacterium responsible for severe opportunistic infections in humans and animals. We had previously identified a gene encoding a putative UDP-Nacetylglucosamine 2-epimerase, a precursor of the teichoic acid linkage unit, in the genome of L monocytogenes strain EGD-e. This gene, now designated lmo2537, encodes a protein that shares 62% identity with the cognate epimerase MnaA of Bacillus subtilis and 55% identity with Cap5P of Staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 69 publications
(63 reference statements)
5
20
0
Order By: Relevance
“…However, our hmgR construct was able to grow in BHI broth without added IPTG, albeit to a lower extent than when IPTG was present. Our results are similar to those observed by Dubail et al (2006), who reported the first essential gene deletion in L. monocytogenes EGDe but found that there was sufficient gene expression (of lmo2537) from the IPTG promoter to support growth in the absence of the inducer. This demonstrates an essential requirement for hmgR in L. monocytogenes EGDe for in vitro growth, and suggests that low expression of the gene is sufficient to support growth.…”
Section: Discussionsupporting
confidence: 82%
“…However, our hmgR construct was able to grow in BHI broth without added IPTG, albeit to a lower extent than when IPTG was present. Our results are similar to those observed by Dubail et al (2006), who reported the first essential gene deletion in L. monocytogenes EGDe but found that there was sufficient gene expression (of lmo2537) from the IPTG promoter to support growth in the absence of the inducer. This demonstrates an essential requirement for hmgR in L. monocytogenes EGDe for in vitro growth, and suggests that low expression of the gene is sufficient to support growth.…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that phage susceptibility could not be restored by complementation for these mutant strains because their respective mutations had a dominant effect over the respective WT allele; it is also possible that these mutations are not responsible for the observed phage resistance phenotype and that resistance is due to polar effects or other, nonidentified, mutations. However, lmo2537 (the LMRG_01710 homolog in 10403S) encodes UDP-N-acetylglucosamine 2-epimerase, which is a precursor of the teichoic acid linkage unit (61,62). This suggests that LMRG_01709 may have a direct effect on the composition of WTA and phage resistance as LMRG_01709 is part of the same operon as LMRG_01710; however, we cannot definitively exclude a polar effect on LMRG_01710.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, WGS of 69 mutant strains enabled us to observe the parallel evolution of phage resistance in L. monocytogenes 10403S under the selective pressure of lytic phages, as evidenced by mutations repeatedly and independently occurring in the same genes and causing the same phenotypic effects. As WTA have been shown to be associated with virulence functions (71), including the evidence that a teichoic acid biosynthesis gene is essential for virulence of L. monocytogenes in mice (62), further studies to determine how the mutations found in this study affect virulence, as well as fitness, under a variety of different environmental and stress conditions will be valuable. Additional studies should also examine the frequency of occurrence and stability of the mutations identified here across different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MurA and MurZ, there are three more UDP-GlcNAcconsuming enzymes present in L. monocytogenes (Fig. 6): (i) the essential MnaA protein (encoded by the lmo2537 gene) for the conversion of UDP-GlcNAc into UDP-N-acetylmannosamine, which is part of the teichoic acid linkage unit (26,27); (ii) the wall teichoic acid glycosylation protein GtcA (encoded by lmo2549) (28,29); and (iii) the glycosyltransferase encoded by the lmo2550 gene which is-as GtcAalso required for decoration of wall teichoic acids with GlcNAc (29). We assumed that-for the reasons described above-deletion of gtcA or lmo2550 possibly suppresses the ΔgpsB growth defects as well.…”
Section: Resultsmentioning
confidence: 99%